Chronotype distribution in the Chinese population. Issue 2 (June 2020) - Liu, Zhiwei; Dong, Yingying; Xu, Ying; Zhou, Fei
Purpose: Individual chronotypes are reported to be closely associated with mood, health status, and even disease progression. However, no reports of chronotype distribution in the Chinese population have been made available to date. Methods: We performed a chronotype survey using the classic Morningness–Eveningness Questionnaire both online and offline. The webpage-based online survey was distributed via a social network application on mobile phones. The offline survey was distributed to local primary and middle schools. A total of 9476 questionnaires were collected, of which 8395 were valid. The mean age of the participants was 30.38 ± 11.47 years, and 37.38% were male. Results: Overall, the Chinese chronotypes showed a near-normal distribution with a slight shift toward eveningness. When analyzed in different age groups, the overall Chinese population was shown to be "latest" in their early twenties. In the young population, two significant points of change in chronotype were identified at the ages of 10 and 16 years. The chronotype composition remained relatively stable during early adulthood (from 17 to 28 years of age). Conclusion: This study generated the first overview of chronotype distribution in the Chinese population and will serve as essential background data for future studies.